DNA Methylome and LncRNAome Analysis Provide Insights Into Mechanisms of Genome-Dosage Effects in Autotetraploid Cassava - Liang Xiao; Liuying Lu; Wendan Zeng; Xiaohong Shang; Sheng Cao; Huabing Yan; Huabing Yan (Frontiers in Plant Science, 2022)
Whole genome duplication (WGD) increases the dosage of all coding and non-coding genes, yet the molecular implications of genome-dosage effects remain elusive. In this study, we generated integrated maps of the methylomes and lncRNAomes for diploid and artificially generated autotetraploid cassava (Manihot esculenta Crantz). We found that transposable elements (TEs) suppressed adjacent protein coding gene (PCG)-expression levels, while TEs activated the expression of nearby long non-coding RNAs (lncRNAs) in the cassava genome. The hypermethylation of DNA transposons in mCG and mCHH sites may be an effective way to suppress the expression of nearby PCGs in autotetraploid cassava, resulting in similar expression levels for most of PCGs between autotetraploid and diploid cassava. In the autotetraploid, decreased methylation levels of retrotransposons at mCHG and mCHH sites contributed to reduced methylation of Gypsy-neighboring long intergenic non-coding RNAs, potentially preserving diploid-like expression patterns in the major of lncRNAs. Collectively, our study highlighted that WGD-induced DNA methylation variation in DNA transposons and retrotransposons may be as direct adaptive responses to dosage of all coding-genes and lncRNAs, respectively.